2018
DOI: 10.1093/jxb/ery128
|View full text |Cite
|
Sign up to set email alerts
|

Ethylene responsive factor ERF110 mediates ethylene-regulated transcription of a sex determination-related orthologous gene in two Cucumis species

Abstract: In plants, unisexual flowers derived from developmental sex determination form separate stamens and pistils that facilitate cross pollination. In cucumber and melon, ethylene plays a key role in sex determination. Six sex determination-related genes have been identified in ethylene biosynthesis in these Cucumis species. The interactions among these genes are thought to involve ethylene signaling; however, the underlying mechanism of regulation remains unknown. In this study, hormone treatment and qPCR assays w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
5
1
1

Relationship

1
6

Authors

Journals

citations
Cited by 54 publications
(50 citation statements)
references
References 40 publications
2
48
0
Order By: Relevance
“…Among all three mutant lines, as compared with Gy14, the expression of both CsACS1 and CsACS2 was significantly down regulated, whereas no significant difference in expression was found for CsMYB among the four lines. In our previous study, transcriptome profiling for sex expression revealed no expression difference of the CsBCAT gene among the three mutant lines and Gy14 65 . These data suggest that expression level of both CsMYB and CsBCAT genes at the F locus may have no direct link with gynoecy expression in cucumber.…”
Section: Csacs1mentioning
confidence: 80%
See 1 more Smart Citation
“…Among all three mutant lines, as compared with Gy14, the expression of both CsACS1 and CsACS2 was significantly down regulated, whereas no significant difference in expression was found for CsMYB among the four lines. In our previous study, transcriptome profiling for sex expression revealed no expression difference of the CsBCAT gene among the three mutant lines and Gy14 65 . These data suggest that expression level of both CsMYB and CsBCAT genes at the F locus may have no direct link with gynoecy expression in cucumber.…”
Section: Csacs1mentioning
confidence: 80%
“…S2), but Shiber et al 71 did not detect any transcripts from this putative ORF thus ruling out the possibility that its product may be the F locus. In gynoecious plants (FF), the transcript level of CsACS1/G is much higher 38,65 . On the other hand.…”
Section: Structure and Function Of The F Locus In Cucumbermentioning
confidence: 99%
“…The plant hormone ethylene plays an important role in sex determination in cucumber and counteracts the role of other hormones (Yin and Quinn 1995). Ethylene biosynthesis and its signaling pathway have been the subject of numerous studies that have proven the importance of this hormone in cucumber (Ando et al 2001a, b;Boualem et al 2008Boualem et al , 2009Sun et al 2010;Tao et al 2018;Wang et al 2010;Yamasaki et al 2003a, b).…”
Section: Expression Analysis Of Genes Participating In Ethylene Percementioning
confidence: 99%
“…Whether mRNA or protein or ethylene is the signal finally controlling sex is not known (Boualem et al 2015). Lastly, it was shown that ethylene signals are involved in the regulation of CsACS2 and CsACS11 at the transcriptional level involving CsERF110 (Tao et al 2018).…”
Section: Relationships Between Ethylene and Cucumber Sex Genes-genotymentioning
confidence: 99%
See 1 more Smart Citation